Diversity of Pre-colonial Earthworks in the Brazilian State of Acre, Southwestern Amazonia. (4th July 2018) - Saunaluoma, Sanna; Pärssinen, Martti; Schaan, Denise
ABSTRACT: Amazonian earthworks, which are an important testimony to ancient anthropogenic landscape modifications, have a significant variety of structures and sizes, and are found in different geographical and ecological locations that indicate separate time periods, distinct cultural affiliations, and diverse purposes. We introduce data from diverse archaeological earthwork sites, geoglyphs, mound sites, and walled enclosures situated in the interfluves of the Purus River in the Brazilian state of Acre and propose a type definition for these sites. The abundant anthropogenic landscape features and their associated material culture indicate considerable human-induced environmental alterations and diverse earthworking traditions that are characteristic of the region of eastern Acre from at least ca. 2000b.p. onwards.